BILIOUS VOMITING AS A CLASSICAL CLINICAL MANIFESTATION OF MIDGUT MALROTATION WITH VOLVULUS IN NEONATES: A CASE REPORT - Luh Ayu Lastiyani (Jurnal Impresi Indonesia, 2025)
Vomiting in children can be classified as bile-stained (bilious) or non-bile-stained (non-bilious). Bilious vomiting often indicates serious conditions, such as bowel obstruction or midgut malrotation with volvulus (MMWV), which can lead to bowel ischemia or necrosis. Urgent evaluation is essential, as timely diagnosis can significantly improve the prognosis. We present the case of an 8-day-old baby who experienced bilious vomiting three times, starting one day before hospitalisation. The patient was taken to a community health centre three times due to complaints of bilious vomiting and was eventually referred to Awet Muda Hospital, which in turn referred the baby to West of Nusa Tenggara General Hospital. The infant also exhibited jaundice that appeared two days after birth and had one instance of blood in the urine. Radiological examinations indicated pneumonia, abdominal distension (meteorism), and duodenal stenosis. Laboratory tests revealed hyperbilirubinemia and thrombocytosis. Bilious vomiting is a critical clinical sign indicating potential midgut malrotation with volvulus. It requires immediate evaluation and intervention to ensure the patient's safety and health.